2005
DOI: 10.1074/jbc.m412867200
|View full text |Cite
|
Sign up to set email alerts
|

UV-C Light Induces Raft-associated Acid Sphingomyelinase and JNK Activation and Translocation Independently on a Nuclear Signal

Abstract: The initiation of UV light-induced signaling in mammalian cells is largely considered to be subsequent to DNA damage. Several studies have also described ceramide (CER), a lipid second messenger, as a major contributor in mediating UV light-induced c-Jun N-terminal kinase (JNK) activation and cell death. It is demonstrated here that UV-C light irradiation of U937 cells results in the activation and translocation of a Zn 2؉ -independent acid sphingomyelinase, leading to CER accumulation in raft microdomains. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 45 publications
(52 reference statements)
5
97
0
Order By: Relevance
“…Such observations are consistent with recent findings that translocation of JNK toward lipid raft microdomains occurred when U937 cell was treated with UV-C. 35 In addition, redistribution of MAP kinases, including extracellular signal-regulated kinase and p38, to lipid raft structures in stimulated neutrophils has also been reported, 38 suggesting that membrane lipid rafts may play a role in action of the MAPK family, depending on the study context, such as cell type and the nature of the stimulus. Apoptosis and non-apoptotic cell death/necrosis are two distinct forms of cell death and both are closely implicated in the pathological processes of human diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such observations are consistent with recent findings that translocation of JNK toward lipid raft microdomains occurred when U937 cell was treated with UV-C. 35 In addition, redistribution of MAP kinases, including extracellular signal-regulated kinase and p38, to lipid raft structures in stimulated neutrophils has also been reported, 38 suggesting that membrane lipid rafts may play a role in action of the MAPK family, depending on the study context, such as cell type and the nature of the stimulus. Apoptosis and non-apoptotic cell death/necrosis are two distinct forms of cell death and both are closely implicated in the pathological processes of human diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Although TRAF2 is one of the key molecules in TNFR1 signaling pathway, 11,31 it appears that RNS acts on TRAF2 independent of TNFR1, based on our preliminary observation that tnfr1À/À MEF are as susceptible as WT MEF to RNSinduced cell death (data not shown). Lipid rafts, the liquidordered phase microdomains existing within membranes, have been reported involved in various signaling pathways triggered by numbers of stimuli, such as H 2 O 2 , 12,34 ultraviolet light (UV) 35 and TNFa. 36 Data from our study clearly support the notion that RNS promote the recruitment of TRAF2 into lipid rafts and then mediates JNK activation and subsequent cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been recently shown that generation of reactive oxygen species an important step for aSMase activation in cells (Dumitru and Gulbins 2006;Charruyer et al 2005).The aSMase could be activated by the protein kinase Cδ (PKCδ), which is overexpressed under oxidative stress (Zeidan and Hannun 2007) and a premature aging disorderWerner syndrome (Massip et al 2010). Based on these results, reasonable assumption can be made that α-tocopherol prevents ceramide accumulation in the liver of old rats, at least in part, via the glutathionedependent nSMase and PKCδ-dependent aSMase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when cells are subjected to stress, ASM rapidly translocates from lysosomes to the outer leaflet of the plasma membrane, where it also can hydrolyze sphingomyelin into ceramide [39,40]. This causes reorganization of membrane lipid microdomains, or "raft" structures, and stimulates downstream signaling events.…”
Section: Disease Mechanismmentioning
confidence: 99%